Intravitreal pegaptanib combined with photodynamic therapy in age-related macular degeneration - Turgut, Burak; Kaya, Murat; Çeliker, Ülkü (My University, 2010)
Purpose: To assess the results of photodynamic therapy (PDT) combined with intravitreal pegaptanib (IVP) in the treatment of choroidal neovascularization (CNV) due to age- related macular degeneration (AMD). Materials and Methods: 24 eyes of 21 consecutive patients received IVP combined with PDT treatment between September 2007 to December 2008 were included in this retrospective study. The patients underwent ophthalmological examinations consisting VA, fluorescein angiography (FFA) and optical coherence tomography (OCT) at baseline. PDT was administered and then intravitreal injections were started. Best corrected Snellen visual acuity (BCVA) of the patients converted to log MAR. FFA and OCT analysis was performed at the last visit. Results: Seven patients were female and ten were male, with a mean age of 69.38±8.04 years. BCVA increased or remained stable in 16 eyes (66.7%) and decreased in 8 eyes (33.3%). Four eyes (16.7%) gained three lines or more. At 6 months, mean BCVA improved from 1.34±0.45 (log MAR) to 1.37±0.42 (p=0.26 paired sample t-test). There was no statistically significant BCVA after treatment. No serious ocular or systemic adverse events were observed. Conclusion: The use of IVP combined with PDT in the treatment of subfoveal CNV due to AMD is effective to prevent vision loss. Our data support that this treatment can be alternative because of potential side effects of the drugs that inhibit all VEGF isoforms in the patients recently had stroke or coronary heart diseases and also because of medicolegal or financial problems.
Yaşa Ba?li Makula Dejeneresansinda Fotodinamik Tedavi ile Kombine intravitreal pegaptanib
Keywords: Age-related macular degeneration; Intravitreal pegaptanib; Photodynamic therapy